Spectral Fizeau Interferometer applied to dental polymeric resins early shrinkage determination - Antonacci, Julian (2018)
In this work a variant of the well know Fiber Optic Fizeau Interferometer is presented. It is analyzed in the spectral domain and applied to the study of the shrinkage experienced by photocured polymeric resins. This approach, which maintains its main characteristics of being noninvasive and intrinsically self-calibrated, is sensitive to changes in the direction of evolution of the interferometric cavity length which is being measured. The Spectral Domain Fiber Optic Fizeau Interferometer generates typical response curves that must be processed in order to obtain the measurement related to the cavity length for every moment in time. The cavity is formed between the surface of the sample under test and the fiber optic tip itself. Besides, this sensor is used to determine whether or not exothermal effects from photocuring reactions affect the net shrinkage measured in the samples.